2002
DOI: 10.1001/archpedi.156.5.485
|View full text |Cite
|
Sign up to set email alerts
|

Starting Dose of Levothyroxine for the Treatment of Congenital Hypothyroidism

Abstract: The evidence for an effect of starting dose of levothyroxine on cognitive development, growth, or behavior is too weak to justify recommendations in favor of high- or standard-dose regimens. More reliable information, based on a randomized controlled trial of starting dose or a meta-analysis of the individual patient data currently available, is required to inform treatment policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 53 publications
2
28
0
2
Order By: Relevance
“…Moreover long-term follow-up studies found that high starting dose of L-T4 might cause more behavior problems reflecting increased anxiety, social withdrawal, and poorer concentration (Rovet and Ehrlich, 1995;Oerbeck et al, 2003). The starting dose of L-T4 we used is in conformity with what Campos and Rovet reported, but is much lower than the commonly used dose of 8~15 µg/(kg·d) or the 10.1~15.0 µg/(kg·d) reported from previous studies (Gruters et al, 1997;Hrytsiuk et al, 2002;Salerno et al, 2002). Patients with permanent CH require long-term substitution with a large dose of thyroxin (Rovet and Ehrlich, 1995).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover long-term follow-up studies found that high starting dose of L-T4 might cause more behavior problems reflecting increased anxiety, social withdrawal, and poorer concentration (Rovet and Ehrlich, 1995;Oerbeck et al, 2003). The starting dose of L-T4 we used is in conformity with what Campos and Rovet reported, but is much lower than the commonly used dose of 8~15 µg/(kg·d) or the 10.1~15.0 µg/(kg·d) reported from previous studies (Gruters et al, 1997;Hrytsiuk et al, 2002;Salerno et al, 2002). Patients with permanent CH require long-term substitution with a large dose of thyroxin (Rovet and Ehrlich, 1995).…”
Section: Discussionsupporting
confidence: 79%
“…Clinical and experimental studies have demonstrated that THs are essential for normal brain development. This was documented initially in children with congenital hypothyroidism (Leneman et al, 2001;Hindmarsh, 2002;Hrytsiuk et al, 2002;Salerno et al, 2002;Rovet and Daneman, 2003). These findings were followed by animal studies mainly focused on cerebellar development, which occurs largely postnatally (Koibuchi and Chin, 2000;Thompson and Potter, 2000;Morte et al, 2002;Singh et al, 2003).…”
Section: Nervous Systemmentioning
confidence: 97%
“…16 Indeed, it is not decided what constitutes the best initial dose level, which still remains an issue of considerable discussion, if not controversy. [20][21][22] Studies examining intellectual outcome in children with CH identified by newborn screening describe an average lowering of ϳ6 to 7 IQ points, 23 with values varying according to a number of methodologic factors. Such factors include the particular sample characteristics; treatment and management factors including starting dose and the particular age at which children were treated; test age; and the IQ test that was used and when it was given in relation to when test norms were developed.…”
mentioning
confidence: 99%